Efektivitas Penerapan Sasaran Kinerja Pegawai (SKP)-Online di Lingkungan Badan Pengelola Keuangan dan Aset Daerah (BPKAD) Pemerintah Provinsi Sumatera Utara - Isnaini Faraz Azis Ilmi Sitorus; Azhari Akmal Tarigan (VISA: Journal of Vision and Ideas, 2022)
The focus of this research is to look at the effectiveness of the implementation of Online Employee Performance Targets (SKP) in the Regional Financial and Asset Management Agency (BPKAD) of North Sumatra Province, the inhibiting factors and the efforts made in implementing SKP-Online to improve the performance of the state civil apparatus optimally in Environment of the Regional Financial and Asset Management Agency (BPKAD) of North Sumatra Province. The research uses the theory by Gibson, Donnelly, and Ivancevich regarding organizational effectiveness, then is limited to the application of SKP-Online and employee behavior. This study uses a qualitative method with a descriptive approach. In collecting data, researchers conducted observations, interviews and collected documents related to the application of SKP-Online within the Regional Financial and Asset Management Agency (BPKAD) of North Sumatra Province. The results showed that the implementation of SKP-Online in the Regional Financial and Asset Management Agency (BPKAD) of North Sumatra Province had not run well and optimally, as seen from the implementation process and supervision in the implementation of employee performance targets (SKP)-Online. Then the work environment is less productive and the apparatus resources are still incompetent and the employees' sense of responsibility towards their duties and functions as state civil servants. Efforts were made to improve employee performance in the application of SKP-Online, among others: 1. Creating an innovation by forming a group of employees of the Regional Financial and Asset Management Agency of North Sumatra Province an application on the telephone. 2. Re-socialization to all employees in the Regional Financial and Asset Management Agency of North Sumatra Province, by making a tutorial on the operation of SKP-Online by the editing section. 3. Motivating employees to want to learn how to use and operate technology facilities. Overall, the efforts made have actually been quite good. It's just that over time these efforts have not fully succeeded in improving employee performance in implementing SKP-Online. because these efforts still have not shown a significant impact in building a sense of responsibility of employees towards their duties and increasing work discipline. Therefore, there is still a need for other efforts that are more decisive and have a significant impact to achieve the objectives of implementing SKP-Online, so that the provision of TPP is more efficient and able to optimally improve the quality of employee work and create a competent and quality work environment. Keywords: Effectiveness, SKP-Online and Employee Performance